Crane wheels production quality control - Grigorov, Otto; Gubskiy, Serhy; Okun, Anton (University of Miskolc, 2014)
Quality control of crane wheels is an important part for support of crane mechanisms permanent operation. Normal functioning of logistics systems requires preventing of crane downtimes and delays. The research results of the impact of the crane wheels (710 mm diameter, 65Г steel) surface hardness on coercivity indicators are presented in this paper. Obtained research results of dependence between the coercivity indicators and the crane wheels rolling surface hardness for their use in practice are described. The influence of the crane wheels surface hardness on the coercivity indicators is researched. Research has shown the dependence of the coercive force from the regulatory crane wheels rolling surface hardness, which is received after a quenching. This research allows you to use obtained results for a quality control of the crane wheels quenching in the production process, a rapid control of the crane wheels at the expert examination.
Keywords: crane wheels; rolling surface hardness; coercivity; quality control